Entre a escola e a vida: desafios da ética de si para a experiência formativa - Pagni, Pedro Ângelo [UNESP] (My University, 2011)
This essay aims to analyze the relationship between life and school. In opposition to theoretical perspectives longed for a possible reconciliation between life and school, we look for to show to existing tension between these two spheres, making an analysis of the themes of the experience with birth, death and the difference, and highlight that this reflection invites the subjects of the educational practice to an ethical attitude of care for the other, for oneself and so that the other one takes care of the care of the self. Having the thoughts of Arendt’s and Foucault’s as reference, we understand that life goes beyond school knowledge and practices, offering us what we think about educational practice and making the subjects of that practice learn how to place themselves between life and school, looking for new senses for themselves and resistance to the existent while they transform themselves. Thus, we wait to offer the educators some life problems that pervade the educational practice, reverberate in their experience and make them think about what they have left.

Este ensaio discute a relação entre a vida e a escola. Em oposição às perspectivas teóricas que defendem uma possível conciliação entre vida e escola, evidenciamos a tensão existente entre essas duas esferas, ao analisarmos os temas da experiência com o nascimento, a morte e a diferença, e assinalamos que a sua reflexão convida aos sujeitos da práxis pedagógica a uma atitude ética de cuidado para com o outro, para consigo e para garantir que o outro cuide do cuidado de si mesmo. Tendo como referência o pensamento de Arendt e Foucault, entendemos que a vida ultrapassa os saberes e práticas escolares, oferecendo-nos o que pensar na práxis educativa e fazendo com que os sujeitos dessa práxis aprendam a se localizar entre a escola e a vida, em busca de novos sentidos para eles e de certa resistência ao existente enquanto se transformam a si próprios. Assim, procuramos oferecer aos educadores alguns dos problemas da vida que atravessam a práxis educativa, que repercutem em sua experiência e os fazem pensar sobre aquilo que lhes resta.
Between school and life: challenges of the ethical of self to the formative experience
Keywords: Ética e Educação; formação cultural; Formação de professores; escola; Experiência